Sosialisasi Entrepreneurship Award Tips dan Trik Jenis Usaha Yang Dapat Meraih Pemenang Tingkat Nasional - Mimelientesa Irman; Novita Yulia Putri; Restu Hayati; Desi Mardianty; Lintang Nur Agia; Jansaris Othneil Purba; Syukri Hadi (Institut Bisnis dan Teknologi Pelita Indonesia, 2023)
The form of this activity is socialization of the Entrepreneurship Award as well as information on Tips and Tricks for Types of Businesses That Can Win EA Winners which are carried out on a National Level scale. This activity was carried out by the Riau Islamic University Career Center which invited lecturers from the Pelita Indonesia Business Institute, this invitation was established because IBTPI in 2021 and 2022 managed to win the Entrepreneurship Award. It is hoped that the socialization and information from resource persons (IBTPI lecturers) can motivate and create creative ideas for UIR students/I and also become winners in the EA 2023 later.